How Adult ESL Students Perceive Prior-Experience-Based Instruction - Fujuan Tann; Lee Nabb (Adult Education Research Conference, 2012)
Experience-based education arguably has been widely venerated by adult educators in the United States for several decades (Lindeman, 1926; Dewey, 1938; Knowles, 1970; Kolb, 1984; Mezirow, 1991). Incorporating students‘ prior experience into the learning experience is commonly practiced in this country, and evidence suggests that adult students favor such instructional strategies (Andresen, Boud, & Cohen, 2000; Wlodkowski, 1999, 2004; Vella, 2002). Moreover, globalization as well as ever increasing immigration and international student populations continue to change the composition of adult learners (Institute of International Education, 2011a, 2011b; U.S. Census Bureau, 2010). The U.S. Census Bureau (2010) reported that about 12% of the total population is foreign-born. This population continues to grow and ―is reflected in the ABE and GED classrooms‖ (Larrotta, 2010, p. 199). These circumstances have made the concept of culturally responsive teaching, which espouses teaching to the strengths of culturally diverse students (Gay, 2000; Banks, 2001), progressively pertinent. Research might suggest that students from differing cultures have different instructional strategy preferences (Hofstede, 2001). The kinds of strategies preferred, and whether differences exist in strategy preference between culture groups is pertinent information in the quest to improve and enhance culturally responsive teaching. Such teaching prompts an investigation to discover whether students from other cultures prefer instructional strategies that incorporate prior experience as well. In order to examine these questions, researchers used a mixed method approach to survey 152 students in five different English as a Second Language (ESL) programs across Wyoming to gather information on preferred instructional strategies and how student prior experience should be related to the teaching and learning process. Although results regarding preferred instructional strategies varied between the three main culture groups identified (Hispanic, Asian and Arabic), overall findings indicate that students from these cultures value the incorporation of prior experience in instruction. Results also indicate that students perceive instruction stressing prior experience to promote language learning, personal growth and social identity.